Perancangan Sistem Informasi Jasa Laundry berbasis Android Pada Bio Clean Laundry - Ardhi, Muhammad; Mary, Thomson; Samudra, Ami Anggraini (Universitas PGRI Sumatera Barat, 2022)
Usually the recording of transactions in Bio Clean Laundry is done by writing transactions in a book that has been provided, so that it often causes errors in recording the transaction notes and the results of washing transactions. In addition, there are often discrepancies in the data resulting from transactions so that the business suffers losses. Based on these problems, an Android-Based Laundry Service information system was designed at Bio Clean Laundry using the Unified Modeling Language (UML) modeling language and getting to know programming languages using Block Programming, and the system development life cycle (SDLC) method where this method has planning stages, analysis phase, design phase, implementation phase, testing phase, and maintenance phase. Testing of this information system is done by using blackbox and whitebox methods. Based on testing with the blackbox method, 4 menus were tested with the expected results as many as 12 procedures and 26 results by obtaining a valid percentage of success results. This indicates that all the information system testing scenarios are as expected so that officers can easily record customer data and sales transactions, so this information system can function properly.